2009
DOI: 10.1111/j.1524-475x.2009.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock‐wave therapy enhanced wound healing via increasing topical blood perfusion and tissue regeneration in a rat model of STZ‐induced diabetes

Abstract: Extracorporeal shock-wave therapy (ESWT) has a significant positive effect in accelerating chronic wound healing. However, the bio-mechanisms operating during ESWT of wounds remain unclear. This study investigated the effectiveness of ESWT in the enhancement of diabetic wound healing. A dorsal skin defect (area, 6 x 5 cm) in a streptozotocin-induced diabetes rodent model was used. Fifty male Wistar rats were divided into five groups. Group I consisted of nondiabetic control; group II included diabetic control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
118
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 25 publications
4
118
1
1
Order By: Relevance
“…Our in vivo studies further revealed that ESWT improves wound healing in a rat ischemic skin flap model and that Erk1/2 signaling is involved in this process. Taken together with previous reports (5,16) and with our in vitro and in vivo findings, this suggests that ESWT promotes wound healing by local ATP release and P2 receptor activation that foster cell proliferation and tissue remodeling via Erk1/2 activation.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Our in vivo studies further revealed that ESWT improves wound healing in a rat ischemic skin flap model and that Erk1/2 signaling is involved in this process. Taken together with previous reports (5,16) and with our in vitro and in vivo findings, this suggests that ESWT promotes wound healing by local ATP release and P2 receptor activation that foster cell proliferation and tissue remodeling via Erk1/2 activation.…”
Section: Discussionsupporting
confidence: 50%
“…of ESWT, namely its ability to induce the healing of chronic ulcers and non-healing wounds (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective study, Wang et al (2009) compared the effect of ESWT with that of traditional hyperbaric oxygen therapy on chronic diabetic foot ulcers, and concluded that ESWT achieved better clinical results than hyperbaric oxygen therapy. Although the mechanism underlying low-energy ESWT-mediated improvement of wound healing is not completely known, it is widely thought that its positive effect is mainly related to its role in promoting the revascularization and tissue regeneration in wounds (Kuo et al 2009a).…”
mentioning
confidence: 99%